Policy Implementation of Employment Opportunity for Persons with Disabilities in Pekanbaru City Government Agencies - Daffa Nadya Adriana; Sujianto Sujianto (Publica: Jurnal Pemikiran Administrasi Negara, 2021)
The employment opportunity policy for persons with disabilities is a policy established by the Government which aims to provide employment opportunities and create employment opportunities for persons with disabilities in order to create equal employment rights between persons with disabilities and normal society so that discrimination against persons with disabilities is eliminated. This study aims to look at the implementation of employment opportunities policies for persons with disabilities in Pekanbaru City and the factors that influence the implementation of these policies. The research method used is descriptive qualitative, data collection techniques using interviews, observation, and documentation. This study uses the theory of policy implementation according to Merilee S. Grindle which consists of two indicators that affect the performance of public policy implementation, namely indicators of policy content which include the interests of the target group, types of benefits, degree of desired change, location of decision making, program implementers, resources involved, and indicators of the implementation environment consisting of the powers, interests, and strategies of the actors involved; characteristics of institutions and authorities; compliance and responsiveness. The results of this study are the finding of deficiencies that must be considered to be improved, namely in the aspect of implementing responsiveness (lack of socialization) so that policy implementation has not run optimally in Pekanbaru City. Researchers also found several factors that influence the implementation of this policy in Pekanbaru City, namely the objectives of the policy, human resources, economic conditions, as well as the response and participation of the target group.